Along‐Dip Segmentation of the Slip Behavior and Rheology of the Copiapó Ridge Subducted in North‐Central Chile. Issue 4 (14th February 2022) - Pastén‐Araya, F.; Potin, B.; Azúa, K.; Sáez, M.; Aden‐Antoniów, F.; Ruiz, S.; Cabrera, L.; Ampuero, J. P.; Nocquet, J. M.; Rivera, L.; Duputel, Z.
Abstract: We studied the along‐dip influence of the Copiapó ridge subduction in the Atacama region, North‐Central Chile by building a new seismicity catalog, including similar events and non‐volcanic tremors (NVTs). We also obtained a 3‐D tomographic model for P and S ‐waves velocity (and the implied Vp/Vs ratio). We identify along‐dip segmentation involving four distinct segments: a locked seismogenic zone hosting ordinary seismicity and clusters of similar events; a transition zone with NVTs and low seismicity; an aseismic zone with slow‐slip events; and a deep zone with abundant intraslab seismicity. The velocity models show differences among these zones, with low velocity anomalies of Vp and Vs coinciding with aseismic slip zones, indicating the possible presence of fluids. Due to the spatial distribution along‐strike and along‐dip of the aseismic zones, we propose that these differences in seismogenic behavior are generated by subduction of the heterogeneous seamounts associated with the Copiapó ridge. Plain Language Summary: Several studies suggest that subduction of large bathymetric features such as seamounts and fracture zones can produce aseismic slip in the subduction zones. We investigate the possible influence of the subduction of the Copiapó ridge in north‐central Chile. Our results show down‐dip zones with distinct seismic and aseismic behavior. The seismic zones are distinguished by ordinary seismicity and high coupling values, while the aseismic zones are characterized by low coupling values, clusters of similar events, non‐volcanic tremors and slow‐slip events. In addition, by means of a three‐dimensional tomography model, we suggest that fluids are present in the aseismic zones which can help to produce aseismic slip. All these consistent observations exhibit a significant spatial correlation with the Copiapó ridge. Therefore we propose these differences in the seismic behavior are due to the subduction of the Copiapó ridge. Key Points: We identify distinct along‐dip segments hosting seismicity, clusters of similar events, non‐volcanic tremors and slow slip Low Vp and Vs velocities with moderate Vp/Vs ratio suggest the presence of fluids in the aseismic zones We propose these marked differences in seismic behavior are due to the subduction of the Copiapó ridge